Improving test automation maturity: A multivocal literature review. (15th February 2022) - Wang, Yuqing; Mäntylä, Mika V.; Liu, Zihao; Markkula, Jouni; Raulamo‐jurvanen, Päivi
Abstract: Mature test automation is key for achieving software quality at speed. In this paper, we present a multivocal literature review with the objective to survey and synthesize the guidelines given in the literature for improving test automation maturity. We selected and reviewed 81 primary studies, consisting of 26 academic literature and 55 grey literature sources. From primary studies, we extracted 26 test automation best practices (e.g., Define an effective test automation strategy, Set up good test environments, and Develop high‐quality test scripts) and collected many pieces of advice (e.g., in forms of implementation/improvement approaches, technical techniques, concepts, and experience‐based heuristics) on how to conduct these best practices. We made main observations: (1) There are only six best practices whose positive effect on maturity improvement have been evaluated by academic studies using formal empirical methods; (2) several technical related best practices in this MLR were not presented in test maturity models; (3) some best practices can be linked to success factors and maturity impediments proposed by other scholars; (4) most pieces of advice on how to conduct proposed best practices were identified from experience studies and their effectiveness need to be further evaluated with cross‐site empirical evidence using formal empirical methods; (5) in the literature, some advice on how to conduct certain best practices are conflicting, and some advice on how to conduct certain best practices still need further qualitative analysis. Abstract : This paper reviewed 81 primary studies (26 academic literature and 55 grey literature sources). It extracted 26 test automation best practices (e.g., define an effective test automation strategy, set up good test environments, and develop high‐quality test scripts) and collected many pieces of advice (e.g., in forms of implementation/improvement approaches, technical techniques, concepts, experience‐based heuristics) on how to conduct these best practices.